Voluntary Adoption of Integrated Reporting in an Emerging Market: The Case of UAE - KURDY, DANIA MAHMOUD (2024)
Study Aim The increasing complexity and uncertainty in corporate environments necessitate enhanced transparency, particularly for investors seeking insights into value creation. This study aimed to explore the factors influencing the voluntary adoption and disclosure of Integrated Reporting (IR) among non-financial companies in the UAE, where IR remains a voluntary practice. Method To achieve this, the research employed a content analysis of integrated reports from 89 non-financial companies listed on the Dubai Financial Market (DFM) and Abu Dhabi Securities Exchange (ADX), utilizing 43 criteria from the IR framework. The study assessed firm-level factors such as profitability, leverage, size, age, and industry, alongside board-level factors including independence, gender diversity, and size. The analysis identified three clusters of disclosure quality—strong, medium, and weak—facilitated by the development of an IR disclosure index tailored to the UAE context. Results The findings indicated that profitability, firm size, and board size significantly influenced IR disclosure quality, with profitability being a consistent determinant across all clusters. Age and gender diversity also impacted disclosure quality but varied in effect across different clusters. These results provide valuable insights for regulators aiming to improve IR practices and for companies seeking alignment with global standards. While this study contributes to the literature on IR adoption in the UAE, its generalizability is limited by sample size and timeframe.